Mortality Rates in Middle and Low-Income Countries - Bacha, Umar (IntechOpen, 2022)
Mortality Rates in Middle and Low-Income Countries describes causes and factors leading to high mortality as well as presents the latest developments in the field of healthcare with best practices to reduce mortality in all ages. It addresses mortality and related health outcomes in economically poor countries and presents a new matric/index for measuring healthcare effectiveness and monitoring levels. It also discusses the burden of non-communicable diseases (NCDs) and the challenges of implementing prevention measures in developing countries. The information in this book can be adopted at various levels to bolster the quality of healthcare systems across the globe.